2013
DOI: 10.1016/j.jneumeth.2013.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Acute reduction in oxygen tension enhances the induction of neurons from human fibroblasts

Abstract: We and others have reported the successful conversion of human fibroblasts into functional induced neuronal (iN) cells; however the reprogramming efficiencies were very low. Robust reprogramming methods must be developed before iN cells can be used for translational applications such as disease modeling or transplantation-based therapies. Here, we describe a novel approach in which we significantly enhance iN cell conversion efficiency of human fibroblast cells by reprogramming under hypoxic conditions (5% O2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The data show that these induced NSC‐like cells express high level of Sox2 and NSC markers such as Pax6 , can be expanded for more than five passages, are capable to differentiate into neurons and glia both in vitro and in vivo (Su et al, ). Interestingly, simple change in oxygen tension (from 21% to 5% O 2 ) during human fibroblasts neural conversion could boost the efficiency of functional iNs generation (Davila et al, ). Developing a system‐level set up that can clarify the regulatory interactions beyond extrinsic and intrinsic factor interplays may help us to provide more powerful transdifferentiation schemes for future cell‐based therapies.…”
Section: Facing the Challenges Toward Flawless Induced Neural Lineagementioning
confidence: 99%
“…The data show that these induced NSC‐like cells express high level of Sox2 and NSC markers such as Pax6 , can be expanded for more than five passages, are capable to differentiate into neurons and glia both in vitro and in vivo (Su et al, ). Interestingly, simple change in oxygen tension (from 21% to 5% O 2 ) during human fibroblasts neural conversion could boost the efficiency of functional iNs generation (Davila et al, ). Developing a system‐level set up that can clarify the regulatory interactions beyond extrinsic and intrinsic factor interplays may help us to provide more powerful transdifferentiation schemes for future cell‐based therapies.…”
Section: Facing the Challenges Toward Flawless Induced Neural Lineagementioning
confidence: 99%
“…Hypoxic conditions during the initial reprogramming stages significantly enhance the efficiency of inducing human fibroblasts into neuronal cells[19]. Mouse fibroblast cells were transdifferentiated into an intermediate state characterized by spherical cell aggregates, somewhere between mouse embryonic stem cells and mouse fibroblasts, using specialized medium containing lipid-rich albumin.…”
Section: Introductionmentioning
confidence: 99%
“…These data demonstrate that miR-124.T-regulated vectors stably convert human fibroblasts to induced neurons at the same efficiency and purity as nonregulated vectors, without significant effects on subtype specificity. It is worth noting that the conversion efficiency is remarkably high in these experiments compared to most other published studies (Ambasudhan et al, 2011;Caiazzo et al, 2011;Davila et al, 2013;Pang et al, 2011;Pfisterer et al, 2011a;Wang et al, 2014;Yoo et al, 2011), and on par with the highest conversion efficiencies that have been reported using doxycycline-regulated vectors (Ladewig et al, 2012;Liu et al, 2013;Pereira et al, 2014). One likely explanation for this is the use of phosphoglycerate kinase (PGK) promoter in these studies.…”
Section: Resultsmentioning
confidence: 62%